Significant Contribution of the 7th Azad Jammu and Kashmir Legislative Assembly (2001-2006) - Hashmi, Anees Ur Rashid; Gul, Shabnum; Khawaja, Anbrin (Annals of Human and Social Sciences, 2024)
This study is aimed to highlight the contribution of Azad Jammu and Kashmir seventh Legislative Assembly in crucial era: Indo-Pak LoC peace agreements, rehabilitation after earthquake and last tenure of legendary politicians. After foundation the Azad State of Jammu and Kashmir affairs was carried out by rules of business when President was nominated by Muslim Conference until basic democrats’ system was imposed in this State. Democracy advent in this region during presidential elections of 1970 and introducing parliamentary system in Pakistan, the State regulated with Interim Constitutional Act 1973 which modified the in 2021as “Interim Constitution of Azad Jammu and Kashmir”. This study is carried out through historical and analytical methods through primary and secondary sources. It covers efforts of rehabilitations after destructive earthquake. This government is unique as conducted vast legislation to facilitate the public. This governing model must be adopted and series of bills, acts and legislation modified to make AJ&K as welfare state.